Parents' Attitudes and Stress Levels Associated with Assisting Children's Distance Learning in Westren Indonesia - Dina Musila; Florensia Dewi Rahayu Wulan Prasetya; Maria Arnetta Friesca Indriani; Lia Kartika; Agustin Lamtiur (Fakultas Ilmu Keperawatan Universitas Indonesia, 2023)
The Indonesian government implemented distance learning to reduce the viral spread during the coronavirus disease (COVID-19) pandemic. A preliminary study based on interviews with 10 parents found that some parents had problems accessing the internet during their children’s online classes and that they used an excessive amount of data. Parents also had difficulty dividing their time between working and assisting their children with their online learning. This study aimed to determine parents’ attitudes and stress levels associated with assisting their children’s distance learning in western Indonesia. A descriptive research method was utilized, and the research population consisted of parents with school-age children undergoing distance learning in western Indonesia. The accidental sampling technique was used, and 384 respondents were involved. The research instrument was a questionnaire. Univariate analysis was used to analyze the data. The results showed that 1.6% of the respondents had a low stress level, 49.7% had a medium stress level, and 48.7% had a high stress level. The results also revealed that more than half of the respondents (51.3%; n=197) had a positive attitude toward assisting their school-age children during distance learning. Given that this study involved a substantial sample of parents, the findings have implications for academic institutions and community leaders in western Indonesia and similar region. The findings indicate that efforts could be made to educate parents about their stress and attitudes associated with distance learning and the effects these have on their children’s learning.Abstrak Perilaku dan Stres Orang Tua dalam Mendampingi Anak yang Menjalani Pembelajaran Jarak Jauh. Pemerintah menetapkan pembelajaran jarak jauh untuk memutus mata rantai penyebaran COVID-19. Sebuah studi pendahuluan yang melibatkan sepuluh orang tua, ditemukan bahwa beberapa orang tua memiliki masalah dalam mengakses jaringan selama kelas online dengan penggunaan kuota yang berlebihan. Orang tua juga kesulitan membagi waktu untuk bekerja dan mendampingi anak dalam pembelajaran daring. Penelitian ini bertujuan untuk mendeskripsikan sikap dan tingkat stres orang tua dalam mendampingi pembelajaran jarak jauh anak di Indonesia bagian barat. Penelitian ini menggunakan metode penelitian deskriptif, dengan populasi penelitian orang tua dengan anak usia sekolah yang menjalani pembelajaran jarak jauh di Indonesia Barat. Teknik pengambilan sampel yang digunakan dalam penelitian ini adalah accidental sampling sebanyak 384 responden. Instrumen penelitian menggunakan kuesioner. Teknik analisis data yang digunakan dalam analisis univariat. Hasil penelitian ini menunjukkan tingkat stres rendah (1,6%), stres sedang (49,7%), dan stres tinggi (48,7%). Penelitian ini juga mengungkapkan bahwa lebih dari separuh responden memiliki sikap positif terhadap pendampingan anak usia sekolah selama pembelajaran jarak jauh, yaitu sebanyak 197 responden (51,3%). Penelitian ini melibatkan sampel orang tua yang cukup besar, sehingga temuan-temuan yang ada memiliki implikasi bagi institusi akademis dan tokoh masyarakat di Indonesia bagian barat dan wilayah serupa. Upaya-upaya dapat dilakukan untuk mengedukasi orang tua mengenai stres dan sikap mereka terkait pembelajaran jarak jauh dan dampaknya terhadap pembelajaran anak-anak mereka. Kata Kunci: orang tua, pembelajaran jarak jauh, perilaku, stres